2008
DOI: 10.1093/nar/gkn184
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA ligases I and III, but not ligase IV, are required for microhomology-mediated end joining of DNA double-strand breaks

Abstract: DNA nonhomologous end-joining (NHEJ) and homologous recombination are two distinct pathways of DNA double-strand break repair in mammalian cells. Biochemical and genetic studies showed that DNA ends can also be joined via microhomology-mediated end joining (MHEJ), especially when proteins responsible for NHEJ, such as Ku, are reduced or absent. While it has been known that Ku-dependent NHEJ requires DNA ligase IV, it is unclear which DNA ligase(s) is required for Ku-independent MHEJ. In this study, we used a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 45 publications
3
91
0
Order By: Relevance
“…Further, we confirmed the differential activity of HR and NHEJ pathways in mESC and fibroblasts by in vitro functional assays [39][40][41]. Recombination reactions using nuclear protein extracts prepared from exponentially growing cells showed a 3-fold increase in HR activity in mESC compared to primary fibroblasts (P value <0.001; Fig.…”
Section: Differential Activity Of Hr and Nhej Repair Pathways In Mescsupporting
confidence: 73%
See 1 more Smart Citation
“…Further, we confirmed the differential activity of HR and NHEJ pathways in mESC and fibroblasts by in vitro functional assays [39][40][41]. Recombination reactions using nuclear protein extracts prepared from exponentially growing cells showed a 3-fold increase in HR activity in mESC compared to primary fibroblasts (P value <0.001; Fig.…”
Section: Differential Activity Of Hr and Nhej Repair Pathways In Mescsupporting
confidence: 73%
“…The NHEJ in vitro assay was conducted as described by Liang et al [40,41]. Briefly, the linearized DNA substrate was incubated with nuclear protein extract in 50 mM Tris-HCL (pH 7.6), 10 mM MgCl 2 , 1 mM dithiothreitol, 1 mM ATP, and 25% polyethylene glycol 8000 at 148C for 2 h. Aftr the reaction, DNA was deproteinized and purified by using a PCR purification kit (Qiagen).…”
Section: In Vitro Assay For Nhejmentioning
confidence: 99%
“…In yeast and human cells, LIG4 mediates double-strand ligation during NHEJ [46,47], and Lig3 is considered a necessary factor for homologous end ligation [7,21,22]. We next determined which ligases are required for MMEJ activity in zebrafish embryos.…”
Section: Zebrafish Mmej Is Dependent On Ligase 3 But Independent Of Lmentioning
confidence: 99%
“…By contrast, NHEJ is the most straightforward way to repair a DSB, as the broken ends are simply rejoined regardless of the genetic sequences at the break. Efficient NHEJ is most active during G1 and early S phase, and it requires Ku70/Ku80 heterodimers, DNA-PK catalytic subunits in mammalian cells have shown that PARP-1, ligase 3, CtIP, and Mre11 can promote MMEJ [7,11,[21][22][23][24]. Nevertheless, how often MMEJ occurs during vertebrate development and which type of ligase is required for MMEJ repair in vivo remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, variants in genes involved in DNA DSB repair are considered tobe good candidates for breast cancer susceptibility. LIG4 encoding the protein DNA Ligase IV, is a human ATP-dependent DNA ligase TMR, the rate of total mutation; CMR, the rate of complete mutation; PMR, the rate of partial mutation; OR, odds ratio; 95%CI, 95% confidence interval gene that plays a significant role in joining double-strand breaks during the NHEJ pathway of double-strand break repair (Liang et al, 2008 (Dapic et al, 2005). However, Kuschel et al indicated that Ligase IV can decrease the risk for breast cancer.…”
Section: Discussionmentioning
confidence: 99%